2014
DOI: 10.1016/j.jvs.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of urgent carotid endarterectomy for stable and unstable acute neurologic deficits

Abstract: Our results with U-CEA confirm that this population has a higher risk profile compared with elective surgery. The type of acute presentation is correlated with perioperative risk. U-CEA was safe when performed on patients presenting with transient ischemic attack. An acceptable complication rate was achieved for patients with minor to moderate strokes. The poorest outcomes occurred in patients presenting with stroke in evolution: U-CEA in these patients should be offered with extreme caution, although we are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 28 publications
2
16
0
8
Order By: Relevance
“…However, no differences were found on comparing the reference group (3-7 days) to the other time interval groups (8-14 days: risk ratio, 1.12; 95% confidence interval, 0.62-2.02; 15-180 days: risk ratio, 1.90; 95% confidence interval, 1.12-3.22). 10 One reason for the different findings may be the fact that at least some emergency procedures such as crescendo-TIA or stroke-in-evolution, which carry a markedly higher risk of stroke or death, 22,25 were not excluded from the latter study. In this regard, a systematic review revealed a pooled absolute risk of stroke and death after CEA in patients with crescendo-TIA of 11.4% (95% confidence interval, 6.1-16.7; n=301) and 20.2% (95% confidence interval, 12.0-28.4; n=135) in patients with strokein-evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were found on comparing the reference group (3-7 days) to the other time interval groups (8-14 days: risk ratio, 1.12; 95% confidence interval, 0.62-2.02; 15-180 days: risk ratio, 1.90; 95% confidence interval, 1.12-3.22). 10 One reason for the different findings may be the fact that at least some emergency procedures such as crescendo-TIA or stroke-in-evolution, which carry a markedly higher risk of stroke or death, 22,25 were not excluded from the latter study. In this regard, a systematic review revealed a pooled absolute risk of stroke and death after CEA in patients with crescendo-TIA of 11.4% (95% confidence interval, 6.1-16.7; n=301) and 20.2% (95% confidence interval, 12.0-28.4; n=135) in patients with strokein-evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This surgery is considered to be at high risk. Nevertheless, several small monocentric studies reported favourable outcomes, including patients with major strokes during acute phase [15,17,18]. Lesèche et al 2012; reported no death or postoperative stroke for 27 patients who underwent CR during the acute phase of stroke with a median delay of six days from symptom onset to surgery [13].…”
Section: Discussionmentioning
confidence: 99%
“…Their results should be interpreted taking into account the postoperative risks related to the severity of the initial lesion. For example, for Barbetta et al 2014; the 30-day outcomes of early CR in 90 patients were considered as satisfactory despite four deaths and six postoperative strokes. In their series, half of the complications occurred in 11 patients who presented with severe stroke in evolution [15].Nevertheless, in many series, results suggest that early CR after brain infarct is safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that 25% of strokes are preceded by a TIA, and 45% of the TIAs occur the week prior 71. Interestingly, carotid intervention for patients with a stroke-in-evolution (worsening symptoms over the course of hours to days) is unclear,72,73 with poor outcomes for patients with stroke-in-evolution, regardless of medical or surgical management 72…”
Section: Carotid Endarterectomy In Symptomatic Patientsmentioning
confidence: 99%